Subtitusi Dedak Halus pada Pakan Jangkrik Kalung (Gryllus bimaculatus) - Hutabarat, A. L. R.; Endrawati, Y. C.; Fuah, A. M. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2013)
This research was aimed to analyze the effect of refined rice bran as feed subtitutions on the growth of kalung cricket (Gryllus bimaculatus). The animal used were 3000 kalung crickets that given commercial feed subtituted by 0% (R1), 25% (R2), 50% (R3), 75% (R4), and 100% (R5) refined rice bran. Each treatment was repeated four times. Data analyzed using Randomized Complete Design with variables consist of: 1) feed consumption, 2) body weight, 3) body weight gain, 4) feed convertion and 5) mortality rate. The subtitution of 25-50% of refined rice bran showed the highest body weight and body weight gain at the age of 30-40 days compared to the others treatments. Crickets of 50 days of age that were given 100% of commercial feed or 0% refined rice bran subtituted reached the highest body weight and body weight gain. Crickets at the age of 30-40 days of age had a higher feed efficiency and lower feed convertion compared with 50 days of age crickets.